Matrine enhances the inhibitory effect of 5-FU on SW480 cells in vitro and in vivo - Xu, Hui Zhang; Lei, Liang; Xiao, Yan Wang; Li, Zhang; Yan, Xin Zheng; Hong, Zhu Deng; Xin, Rong Wu (Universiti Kebangsaan Malaysia, 2016)
We investigated the antitumor effects of the combination of matrine-a purified alkaloid extracted from Sophora flavescence-and 5-fluorouracil (5-FU) on SW480 cells. This combination inhibited the growth of SW480 cells in a synergistic or additive manner by disrupting their progression through the cell cycle. Exposure of SW480 cells to matrine and 5-FU was followed by an increased rate of expression for caspase-3, caspase-9 and poly-ADP ribose polymerase (PARP) and inhibited the subcutaneous transplantation of SW480 tumors into Balb/c nude mice. Histopathological analysis showed that this effect was most pronounced in the spleens of treated animals. Typical cytotoxic effects observed in 5-FU-treated mice included fibrosis and lymphopenia, whereas in mice treated with 5-FU combined with matrine, the spleen ultrastructure remained intact. These findings indicate that matrine may enhance the therapeutic effectiveness of 5-FU in SW480 tumors by enhancing apoptosis and overcome the threat to immunocompetence associated with 5-FU.